(untitled) (Acta Polytechnica CTU Proceedings, 2017)
Presented contribution is dedicated to discussion of two different approaches into increase of programming language safety. They are language subset and extension of original safety mechanisms. As examples we used MISRA C/C++ subset and SPARK language builded on the base of ADA language. In the last chapters we discuss novel approaches based on application of programmable hardware which is described in VHDL language, which is also modification of ADA language. Especially SPARK and VHDL languages represents novel approaches to safe system development which are now discussed in relation to new Railway SW projects.